Correction: Aging and the relationships between long-axis systolic and early diastolic excursion, isovolumic relaxation time and left ventricular length-Implications for the interpretation of aging effects on e`. - Roger E Peverill (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0210277.].